2003
DOI: 10.1354/vp.40-3-254
|View full text |Cite
|
Sign up to set email alerts
|

A Histopathologic, Immunohistochemical, and Ultrastructural Study of the Intestine in Pigs Inoculated with Classical Swine Fever Virus

Abstract: The aim of this study was to report on the lesions occurring in the intestine during experimental classical swine fever (CSF) and to clarify the nature of infected cells and the distribution of viral antigen. Thirty-two pigs were inoculated with the virulent CSF virus (CSFV) isolate Alfort 187 and slaughtered from 2 to 15 postinoculation days; four animals of similar background served as a control group. Immunohistochemistry, electron microscopy, and the transferase-mediated deoxyuridine triphosphate nick-end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
2
20
1
Order By: Relevance
“…Although other studies attribute lymphoid depletion to necrosis, 31,32 recent research has shown that lymphocyte death in CSF is due to apoptosis. 6,41,42,47 The results obtained in this study suggest that the direct virus action on lymphocytes, described in previous studies, 6,32 is not responsible per se for the massive lymphoid depletion in the spleen, but rather, that it plays a secondary role; infection of lymphocytes is certainly observed, but it occurs following the death of these cells. The small number of infected lymphocytes does not tally with the considerable lymphoid depletion exhibited by affected animals, but this depletion does coincide with the numeric increase and secretory activation in m-Møs.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Although other studies attribute lymphoid depletion to necrosis, 31,32 recent research has shown that lymphocyte death in CSF is due to apoptosis. 6,41,42,47 The results obtained in this study suggest that the direct virus action on lymphocytes, described in previous studies, 6,32 is not responsible per se for the massive lymphoid depletion in the spleen, but rather, that it plays a secondary role; infection of lymphocytes is certainly observed, but it occurs following the death of these cells. The small number of infected lymphocytes does not tally with the considerable lymphoid depletion exhibited by affected animals, but this depletion does coincide with the numeric increase and secretory activation in m-Møs.…”
Section: Discussionsupporting
confidence: 61%
“…8 Attention is also drawn to the procoagulant activity of both TNF-␣ and IL-1 and, to a lesser extent, IL-6, 16,46 as well as to the involvement of TNF-␣, together with tissue damage, in the activation of the extrinsic coagulation pathway. 52 Numerous studies have shown that the m-Mø is the prime target cell of classical swine fever (CSF) or hog cholera virus, 21,41,42,47 although lymphocyte infection is also reported in later stages of the disease. 21,47,49 The pathogenic mechanisms involved in the thrombocytopenia and lymphoid depletion observed in CSF remain unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CSF has severe consequences on animal welfare, livestock production, trade and national economy [4]. During CSFV infection immunosupression refl ected in depletion of lymphocytes in lymphoid organs occurs, while severe lymphopenia is present [5][6][7][8][9][10]. Lymphocytes, monocytes, immature granulocytes as well as endothelial cells, have been recognized to be infected with CSFV, consequently leading to morphological changes in various tissues [11].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic CSFV infections can last up to 100 days (51). N pro might allow the virus to persist in a particular cell type or organ, for example, in vascular endothelial cells (6), lymph nodes, spleen, and intestine, in particular the gut-associated lymphoid tissue (10,42). It is also possible that N pro is important for establishing persistent infections in offspring of animals infected during pregnancy.…”
mentioning
confidence: 99%